Late prehistory and protohistory, Volume 9, Sessions A3c and A16a Bronze Age and Iron Age : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain) - Coimbra, Fernando 1956-; Delfino, Davide 1976-; Sîrbu, Valeriu 1950-; Schuster, Cristian 1959- (Archaeopress Archaeology, 2016)
This work contains the proceedings of two sessions from the XVII UISPP World Congress, 2014